Impact of capacitor dielectric relaxation on a 14-bit 70-MS - Zanchi, A. (IEEE Journal of solid state circuits)
In this paper, phenomena of charge absorption and relaxation in the plasma enhanced chemical vapor deposition (PECVD) silicon nitride dielectric (Si3N4) used in the capacitors of a 45-GHz fT, 0.4-μm Lmin SiGe BiCMOS are observed and interpreted. When such capacitors are used to design a pipelined 14-bit 70-MS/s switched-capacitor analog-to-digital converter (ADC), dielectric relaxation is identified as the cause of 8-LSB-wide gaps in the integral nonlinearity, which leads to the degradation of the converter performance even at low frequencies. The effect has been analyzed via Matlab behavioral simulations and SPICE circuit simulations. Ad-hoc experimental tests aimed at detecting residual amounts of charge left in the capacitors as a memory of previous states have been also carried out. After low-density low-pressure chemical vapor deposition (LPCVD) oxide capacitors (SiO2) are introduced in the process, a new ADC test chip delivers 72.5-dBFS SNR, 82-dBc SFDR, 11.7-bit ENOB at 70 MS/s and 1-MHz input. The circuit features a die size of 5.3 × 5.3 mm2 and dissipates 1 W from the 3.3-V supply.